(3JMaI GdWGdH HeYQaI ef jfJSH Edi YHO Gddg CHj GdfHi Udi Gddg Ydjg hSde hGHi WGdHs - (3MSjf Hf YHO Gddg Hf GdMSjf GdeTQa Gdeci GdMSjfi GdSeQbfOi ,(B1043 (3g`s
(3ChdgG (B:s
(3hHYO agPg JMag GdWGdH HeYQag ef jfJSH Edi YHO Gddg hCHi WGdH CPcQ ajgG aQhYgG haQhY aQhYge s
(3BNQgG (B:s
(3hgPG BNQ eG ChQOfG ajef jfJSH Edi YHO Gddg CHj GdfHi Udi Gddg Ydjg hSde hEdi CHj WGdH CHj YHO GdeWdH Hf gGTe s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B97 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs